2016
DOI: 10.18203/2394-6040.ijcmph20163946
|View full text |Cite
|
Sign up to set email alerts
|

Spirometric evaluation of the pulmonary functions in the petrol pump workers of Jaipur city, Rajasthan, India

Abstract: Background: With rapid urbanization and economic development, occupational health hazards have grown as one of the major public health challenges. Many groups in the society are at greater risk of developing adverse consequences owing to their working environment, one such group is the petrol pump workers who by virtue of their occupation are continously exposed to the noxious chemical compounds present in gasoline. Hence, this study was undertaken to find out the effects of gasoline vapors on pulmonary functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(8 reference statements)
2
1
0
Order By: Relevance
“…There was no signi cant correlation between duration of work (hrs/day) and PEFR. This result is quite similar to Rahul,et al, who also found insigni cant correlation between PEFR and duration of work in hours per day [13] and Diise et al who revealed signi cant association between work duration and lung function parameters except PEFR[8].However, it has been found that workers who spent more hours per day had a signi cant impairment in lung function test (p. value = 0.05)[6].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…There was no signi cant correlation between duration of work (hrs/day) and PEFR. This result is quite similar to Rahul,et al, who also found insigni cant correlation between PEFR and duration of work in hours per day [13] and Diise et al who revealed signi cant association between work duration and lung function parameters except PEFR[8].However, it has been found that workers who spent more hours per day had a signi cant impairment in lung function test (p. value = 0.05)[6].…”
Section: Discussionsupporting
confidence: 86%
“…A preceding study by Rahul, et al, also showed no signi cant association between spending duties at early morning, mid-day, evening and late night with lung functions. [13] The present study showed that 70% of workers had abnormal PEFR. A signi cant reduction (p < 0.0001) in the mean PEFR was found in the petrol pump workers as compared to the standard normal values.74% of the petrol attendants were found to have reduced PEFR values [14].…”
Section: Discussionsupporting
confidence: 52%
“…Gasoline contains more than 150 chemicals including benzene, toluene, xylene, and phenolic compounds such as VOCs and PAHs (Shaikh et al ., 2018). Studies in different countries reported that fuel filling station attendants are continuously exposed to petroleum components through skin contact, inhalation and chronic exposure may cause respiratory, blood disorders, and genotoxicity (Cezar‐Vaz et al ., 2012; Abou‐El Wafa et al ., 2015; Rahul et al ., 2016; Xiong et al ., 2016). The present study focused on monitoring workplace pollutants and genotoxicity effects among fuel filling station workers.…”
Section: Discussionmentioning
confidence: 99%